Process of linking the Human Resource to be hired by the Regional Educational Innovation Center Oriente -CIER Oriente-, in the city of Villavicencio - by Viviana Pérez (GEON Journal (Management, Organizations and Business), 2015)
The aim of this work is to develop a management degree proposal that guides a process of linking human resources to hire by the Center on Education Innovation Regional East- East -CIER in the city of Villavicencio. The proposal is framed within administrative theories processing threads such as recruitment , selection and hiring of human resources necessary for the development of linkage staff, which has been characterized by information gathering , updating and improvement mechanisms . The development of the proposal involves the participation of employees in the CIER East and regulatory bodies such as the Universidad de los Llanos in Villavicencio and the Ministry of Education.
Keywords: East- Regional Educational Innovation Center; National Education Ministry; Human Resources; Recruiting; Selection; Hiring